The evaluation of in-hospital prognosis of patient with myocardial infarction and atrial fibrillation. (11th May 2021) - Leonova, I; Solovyeva, M; Boldueva, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Purpose:  to assess the incidence of various forms of atrial fibrillation (AF) among the patients with MI, the prevalence of various types of myocardial infarction (MI) among the patients with AF, the features of the in-hospital prognosis among the patients with MI, and AF compared with those without AF. Materials and methods:  1660 cases of patients with MI treated in 2013-18 - the main group (100 patients) were analyzed.  Results:  AF occurred in 309 patients (18.6% of the total number of patients with MI). Preexisting AF was in 59.2% of patients. Patients with MI and AF were older than those without AF (mean age 75.2 ± 10.1 versus 64.6 ± 12.8, p <0.0001), among them there were more women (52.4% versus 35.5% in patients without AF, p <0.0001). Type 2 MI occurred 5 times more often among patients with MI and AF (p <0.0001). Further, 2 study groups were formed - the main (100 patients with type 1 MI and preexisting AF) and control (type 1 MI 200 patients without AF), adjusted for sex (58% of women in both groups), age (mean age 75.5 ± 8, 7 in the main group versus 75.2 ± 8.5 in the control group, p = 0.775). DM (45% versus 31.5%, p = 0.030), previous MI (40% versus 25.5%, p = 0.012) and stroke (21% vs. 11.5%, p = 0.037) were more common in the main group than in the control. Patients with MI and AF had lower GFR (56.8 ± 19.4 versus 61.7 ± 17.9 ml / min / 1.73 m2, p = 0.031), LDL (2.8 ± 0.9 versus 3.3 ± 1.0 mmol/L, p = 0.0002). Patients with AF had a lower left ventricular ejection fraction (55.2 ± 10.5 versus 59.8 ± 10.0 %, p = 0.0005). Significant mitral regurgitation was more common in the 1-st group (53.9% versus 30.3% in the control group, p = 0.0002). There were no significant differences in the incidence of acute heart failure (HF) (Killip 3-4) (20% versus 13%, p = 0.127). Patients in the 1-st and 2-nd groups did not differ in the number of affected coronary artery (p = 0.7327), the level of their damage (p = 0.1956), in the frequency of revascularization (p = 0.0686). Patients with MI and AF had worse in-hospital prognosis. Pulmonary embolism (PE) (9% in patients with AF versus 1% in patients without AF, p = 0.0011), minor bleeding (21% versus 9.5%, p = 0.0057), combined endpoint (stroke + PE + mortality) (19% versus 10.5%, p = 0.0415) were more common in the main group. At discharge, patients with AF had chronic HF III NYHA in 21.8% cases versus 5.5% in patients without AF, p = 0.0001. There were no significant differences in other endpoints (recurrent MI, stroke, major bleeding, and total mortality) between the groups during hospitalization. In-hospital mortality was 13% in the main versus 9.5% in the control group (p = 0.4276). Conclusion:  AF occurs in 18.6% of patients with MI. Patients with AF and MI are older with the prevalence of females. Patients with type 1 MI and pre-existing AF is a group of high risk. PE, severe chronic HF, minor bleeding, and combined endpoint (stroke + PE + mortality) were significantly common among them.